Modern transformation of the subject as an ontological revolution - Victor Levytskyi (Cхід, 2017)
In this article author substantiates a statement, according to which during a process of modern mind’s search for the substitution for religious principles of thinking and being transcendental conditions of experience of cooperation with the world have been stated and along with this a new type of subject-object relation has been designed (legitimized) and a new form of social reality has been created. There’s also been given opinions of Heidegger, Jean Grondin, N. Candlemas and Karl Jaspers on the formation and consolidation of secularization’s new senses and new subjects of action. It’s been showed that the foundation of a new being was drawn towards personality and immanence (Ego of Descartes, transcendental subject of Kant, Fichte’s I) and formed bases of anthropologic discourse. Exactly in Descartes’ philosophy a person becomes subject and also raises a question of subjectivity's principles; in Kant’s philosophy a person becomes a bearer of creative activity, a subject and “legislator” of the world order, which he is only able to cognize. Along with this, a formation of a new transcendental foundation for cultural forms, one of which was an immanent subject,  didn’t happen in a form of a unified and directed at one goal process, but was a part of a common movement of secularization of Western civilization’s senses. A conversion to the immanent subject as an indisputable reason for cognitive processes and development of the science of a new age conformed to changes in European thinking, because of which philosophers stopped developing theoretical knowledge basing on the appeal to the divine reality and “logical” subject of antiquity and Middle Ages has been replaced by thinking and operating subject of a new reality, relations with which defined a civilization face of a modern age.